2008
DOI: 10.1017/s1049023x00006336
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Related Injuries: Assessment of 854 Victims of the 2003 Bam Disaster Transported to Tertiary Referral Hospitals

Abstract: Background:In December 2003, the residents of Bam, Iran experienced an earthquake that measured 6.6 on the Richter scale and destroyed >90% of the city. After the assessment and initial treatment of injuries at national and international field hospitals, a considerable number of victims (approximately 12,000) were transferred to tertiary referral hospitals around the country. Objective: This report evaluated the injuries of 854 victims transferred to 12 referral hospitals in Tehran.Methods:The demographic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 17 publications
7
28
0
1
Order By: Relevance
“…1). As expected, extremity injuries and head injury were the most common injury encountered, in keeping with the usual pattern of injury seen in survivors of major earthquakes (Qiu et al 2010;Salimi et al 2009;Mohebbi et al 2008). …”
Section: Immediate Response Post Earthquakesupporting
confidence: 77%
“…1). As expected, extremity injuries and head injury were the most common injury encountered, in keeping with the usual pattern of injury seen in survivors of major earthquakes (Qiu et al 2010;Salimi et al 2009;Mohebbi et al 2008). …”
Section: Immediate Response Post Earthquakesupporting
confidence: 77%
“…Mohebbi et al reported that there were 467 men (54.7%) and 387 women (45.3%) injured in the Bam earthquake 2003. According to the report by Peek-Asa et al, however, the Bam earthquake (10) which occurred in 2003 demonstrated that women were more vulnerable than men to earthquake injuries with a 2.4 times higher injury risk (8). In our study, older women were more likely to be injured.…”
Section: Discussionmentioning
confidence: 99%
“…Amputation rates after earthquake vary. In Bam, published reports indicate a range from 0.4%–2.9%7 24 for some hospitals, but rates as high as 10.8%8 were indicated for patients treated in tertiary hospitals. Reports from the Kashmiri earthquake reveal rates of 0.6%–3.6%25 26 recorded in some hospitals.…”
Section: Observationsmentioning
confidence: 99%